Comparative Study between Conservative Management and Appendectomy in Appendicular Lump in Children - Khan, Feeroz Alam; Paudel, Nabin; Maharjan, Prabir (Journal of Nepalgunj Medical College, 2021)
Introduction: Acute appendicitis is the most common presentation in the pediatric emergency department. Presentation ranges from mild inflammation to perforation and peritonitis. Frequently, patients present late with lump formation. Traditionally, an appendicular lump is managed conservatively followed by interval appendectomy six weeks later when the inflammation has resolved. Aims: This study was designed to evaluate the outcome of early appendectomy in cases of appendicular lump and their complications compared to the conventional method of conservative management followed by interval appendectomy. Methods: A prospective comparative study was conducted between November 2018 and October 2021. All the patients with appendicular lump of up to 7 days duration diagnosed clinically or by ultrasonography were randomly divided into two groups. Group I patients were conservatively managed as per the Ochsner-Sherren regimen. Patients in Group II were operated within 24 hours of admission. Mean operative time was recorded in each case. Complications following the respective interventions were observed. Results: Sixty-two patients of which 42 males and 20 females were diagnosed to have an appendicular lump. The age of the patients ranged from seven to 15 years. Duration of onset ranged from three to seven days at the time of presentation in the emergency room. All the patients in Group I except two patients underwent conservative management. There were four readmissions among Group I patients and one in Group II. The average operating time was 67 minutes for patients undergoing open appendectomy. Complications following surgery were more in patients presenting with history of over five days duration. Group I patients had a comparatively greater number of hospital admission days compared to Group II (7.1 and 4.8 days). Conclusion: The appendicular lump can be explored early as it confirms the diagnosis, shortens the financial burden and hospital stay and avoids follow-up visits for interval surgery.